Design of Health Application Prototype "Medimate" Using Design Thinking And System Usability Scale (SUS) - Frank Emmanuel Wuaten; Djoni Hatidja; Mahardika Inra Takaendengan; Edwin Tenda; Christian Alderi Jeffta Soewoeh; Wisard Widsli Kalengkongan (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2026)
The rapid digitization of healthcare in Indonesia reveals significant usability gaps, with popular applications like Halodoc and Alodokter showing inconsistent System Usability Scale (SUS) scores. Specifically, existing platforms often prioritize feature completeness over user-centered interface design, resulting in navigation ambiguities. Background information highlights that poor UX leads to user abandonment. Therefore, optimizing interface design is crucial. This research aims to design a user-centered health application prototype, "Medimate," to address critical interface and navigation deficiencies. The study employs a mixed-methods approach, utilizing the five-stage Design Thinking framework (Empathize, Define, Ideate, Prototype, Test) for development and SUS for quantitative evaluation. Data collection involved in-depth interviews with two user personas to identify pain points, followed by usability testing with 36 respondents. Responses were collected via Google Forms to facilitate remote data gathering. Results indicate that "Medimate" effectively resolves identified UX issues, achieving a mean SUS score of 80.42, classified as Grade A- (Excellent). Key design improvements include transparent pricing structures, intuitive navigation flows, and integrated mental health features. The study concludes that the Design Thinking approach significantly enhances usability metrics in health applications. "Medimate" demonstrates high acceptability and viability for further functional development. Future research should expand sample sizes to include broader demographics and evaluate backend performance. This study contributes a validated design framework for improving digital health accessibility in emerging markets.